Ecology and structure of Drosophyllum lusitanicum (L.) Link populations in the south- western of the Iberian Peninsula - Müller, Jonas; Deil, Urlich (Acta Botanica Malacitana, 2001)
The population size and the demographic structure of the autogamous and nautochoric Drosophyllum lusitanicum were studied in two areas in the South-western Iberian Peninsula. Its coenological character is documented by a synoptic phytosociological table, based upon the published relevés and new data. In the Serra de Monchique (Portugal), the distribution was mapped. 21 populations are growing there with an average size of 165 individuals. In the Campo de Gibraltar (Spain), the biggest population with severa] thousands of individuals occurs in the Sierra del Aljibe. Plant size, rosette diameter and lignification rate from 700 measured individuals are used as indirect indicators for the age-structure in 19 populations. Drosophyllum has a certain pioneer character. It occurs mostly in open Ericion umbellatae-heathland communities (Stauracantho-Drosophylletum, Querco lusitanicae-Stauracanthetutn, Genisto tridentis- Stauracanthetutn etc.). It is able to colonize disturbed habitats like roadside verges and fire prevention strips and is an apophyt in the Drosophyllo-[Stauracanthenion]-basal community. As a re-seeder the species is favoured by fire events of medium frequency. In open Myrto-Quercetum suberis-woodland and in dense Erica austraiis-heathland, large and tall-growing specimens predominate; there the populations are over-aged. Some deficits in the knowledge of its reproductive biology and further research topics are outlined and the needs for conservation efforts in the Portuguese study area are strengthened.